Fine‐needle aspiration of histoplasmosis in the era of endoscopic ultrasound and endobronchial ultrasound: Cytomorphologic features and correlation with clinical laboratory testing. Issue 9 (15th May 2013) - Gailey, Michael P.; Klutts, J. Stacey; Jensen, Chris S.
Abstract : BACKGROUND: Histoplasmosis has a textbook cytologic description with numerous intracellular organisms that are readily apparent on routine stains. This is based on series and reports describing histoplasmosis in immunosuppressed patients with disseminated disease. With the advent of ultrasound‐guided (US) fine‐needle aspiration (FNA) techniques, a marked increase in the cytologic diagnosis of histoplasmosis in immunocompetent patients is noted. METHODS: A search identified all cytology cases diagnosed with Histoplasma within the past 10 years. Cases were reviewed, along with patient demographic, clinical, and laboratory data. RESULTS: A total of 40 FNA cases of histoplasmosis were identified. Patients ranged in age from 15 years to 86 years. There were 23 female patients and 17 male patients; 37 were immunocompetent and 3 were immunosuppressed. Sixteen patients were being staged for primary tumors of other sites; others presented with primary pulmonary symptoms or histoplasmosis was noted incidentally. Specimens were composed of bland acellular necrosis, most commonly with granulomas (77.5%); only rare intracellular organisms were present on routine stains, and variable extracellular organisms were noted on Grocott methenamine silver stain (GMS) stain. GMS stain on direct smears was found to be more sensitive than cell block. Laboratory studies for urine antigen, yeast, and mycelial antibody (by compliment fixation), serum antibody (by immunodiffusion), and culture were positive in 11.8%, 59.1%, 4.5%, 47.6%, and 3.4% of cases, respectively. CONCLUSIONS: In an endemic region, histoplasmosis presents more commonly in immunocompetent patients as localized fibrocaseous disease on FNA and is often identified by high‐resolution imaging. FNA is increasingly used in the diagnosis because of endoscopic ultrasound and endobronchial ultrasound. GMS stain on direct smears is more sensitive than cell block. In general, laboratory tests have low sensitivity in this patient population. Cancer (Cancer Cytopathol) 2013;121:508‐17. © 2013 American Cancer Society. Abstract : A 10‐year experience diagnosing histoplasmosis using ultrasound‐guided fine‐needle aspiration revealed that contrary to recent reports, histoplasmosis was frequently diagnosed in immunocompetent patients when the differential diagnosis commonly included malignancy. In the current study, the cytomorphologic, clinical, and laboratory findings pertinent to the diagnosis are reviewed.